Pemanfaatan Media Powtoon Dalam Pembelajaran Teks Eksplanasi Di Sma Muhammadiyah 1 Imogiri Bantul Yogyakarta - Sintia Pratiwi; Indah Septi Eka Ningrum (PIKTORIAL : Journal of Humanities, 2021)
The purpose of this study was to see the use of the powtoon application as a learning medium for explanatory text at SMA Muhammadiyah 1 Imogiri Bantul Yogyakarta. Indonesia is being hit by the Covid 19 pandemic. All activities that are taking place in the community have stopped, including educational activities. teachers are required to create fun and interactive distance learning. For this reason, researchers use the powtoon application to create fun and interactive learning. in learning using powtoon media there are three stages. the first stage of preparation. In the preparation stage, the researcher prepared material based on predetermined competencies and presented it to the powtoon media. the second stage is the learning stage. at the learning stage, the material is sent via Google Classroom. and the last stage is the evaluation stage. At the evaluation stage, students will be given a questionnaire to measure their level of understanding after learning using Powtoon media.